La marche des femmes - Fournier, Pierre (De lutte en turlutte : une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)
Keywords: amérique du nord; amériques; canada; chanson; discipline; histoire; militance; québec; régions géographiques; sciences humaines; thématiques; travail

La victoire des Midinettes - Fournier, Pierre (De lutte en turlutte : une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)
Keywords: amérique du nord; amériques; canada; chanson; discipline; histoire; militance; québec; régions géographiques; sciences humaines; thématiques; travail

La contribution des femmes à l’histoire de la musique au Québec - Lefebvre, Marie-Thérèse (New Sound, 1998)
Lors d'un colloque international sur les femmes et la création musicale organise par I'Unesco en mars 1996, Mme Zaimont et Mme Ostleitner des Etats-Unis et de I'Autriche, ont démontre dans leur conférence respective á quel point la vie musicale des pays qu'elles représente est encore puissamment dominée par les forces conservatrices et traditionnelles I'Autriche plie sous le poids d'un héritage musical ancestral alors que les Etats-Unis (et jusqu'a un certain point le Canada anglophone) vit actuellement au rythme des tendances politiques de droite. Plusieurs des acquis du mouvement féministe sont actuellement remis en question dans les milieux décisionnels et on ne peut que s'inquiéter de I' impact que pourraient avoir ces mouvements conservateurs sur la création musicale des femmes de ce pays. Mais dans ce même colloque, nous avons également pu entendre les propos de représentantes d'autres pays, je pense ici a la Corée au Japon, a la Bolivie, a I'Uruguay ou les femmes prennent une place de plus en plus importante dans le discours musical et dans la production artistique. De son cote, Le Québec, peut-être a cause de sa situation linguistique et culturelle minoritaire, a développe au cours de son histoire une vitalité artistique enviable et a été a I'avant-garde dans plusieurs domaines dont la création musicale. Le réseau de solidarité que les femmes ont bâti dans le milieu musical depuis quelques années et la place que les compositrices occupent aujourd'hui témoignent de cette vitalité.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; discipline; femmes* artistes; femmes* compositrices; histoire; histoire des femmes*; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Le Red light de Montréal - Proulx, Daniel (VLB éditeur, 1997)
"La légende du défunt quartier montréalais dit du "Red Light" vaut bien celle des Soho et Pigalle de ce monde. Prospères au début du siècle, les salles de jeux enfumées et les chambres sordides de nos bas-fonds deviennent dans les années trente les derniers refuges des damnés de la crise. La guerre venue, les entrepreneurs en plaisirs défendus font des affaires d'or, en attendant que l'armée s'en mêle. La guerre finie, le Red Light renaît en force. C'est alors que Pacifique Plante et Jean Drapeau entrent en scène et procèdent à l'épuration radicale de nos moeurs. Le rideau tombe sur notre quartier "réservé". Aujourd'hui, la "Main" n'est plus qu'un coin de rue, à l'intersection de Sainte-Catherine et de Saint-Laurent. Ni ses habitués ni les passants n'ont idée de son spectaculaire passé." – Quatrième de couverture
Section: 83 pages, [32] pages de planches : photographies en noir et blanc ; 23 cm.
Keywords: 1900-1999; amériques; canada; cours; discipline; his4860; histoire; histoire de la sexualité; histoire et politique; industrie du sexe; montréal; premier cycle; périodes historiques; québec; red light; régions géographiques; révolution tranquille; sciences humaines; sexualité; thématiques; travail; travail du sexe

America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1994)
The Women's Arts Society of Montreal was founded in 1894 by Mary Martha Phillips and Mrs. James H. Peck (nee Mary Alice Skelton). The parent body of the Society (The Women's Art Association of Canada) was incorporated in Toronto in 1892. The goal of the Montreal Society was to integrate women into the art world at a time in history when women had few rights and were relegated to other roles. In 1907, the Montreal branch of the Women's Art Association of Canada broke away from the Toronto organization to form their own independent society. During and after the First World War, the Women's Arts Society of Montreal focussed on philanthropic efforts, assisting disabled and convalescing veterans and their families. After 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In the late 1990s the Society began to accept men as members.
Keywords: 1800-1899; 1900-1999; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montréal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail

II. Une perspective féministe dans l’histoire des congrégations de femmes - Dumont, Micheline (Études d'histoire religieuse, 1990)
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Verso, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Le Bordel: Milieu De Travail Contrôlé - Lévesque, Andrée (Labour / Le Travail, 1987)
PENDANT LONGTEMPS, des milliers de femmes gagnèrent leur vie dans des bordels à Montréal. L'étude de leur milieu de travail pendant les années vingt et trente révèle une organisation hiérarchique et des conditions dont le contrôle échappait aux principales intéressées. L'appareil judiciaire et policier, les organisations de réformes sociales, le clergé et les médecins hygiénistes affectaient, par la tolérance ou la répression, le cadre dans lequel s'exerçait la prostitution. Plus directement, les souteneurs, les tenancières et leurs gérantes déterminaient les conditions quotidiennes de travail. Les changements observés pendant toute cette période sont plus imputables à la vigilance policière qu'aux fluctuations économiques ou aux efforts des travailleuses elles-mêmes.
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; montréal; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; thématiques; travail; travail du sexe; travail du sexe-prostitution

Cheap amusements: Working women and leisure in turn-of-the-century New York - Peiss, Kathy Lee (Temple University Press, 1986)
Contenu: The Homosocial World of Working-Class Amusements – Leisure and Labor – Putting on Style – Dance Madness – The Coney Island Excursion – Cheap Theater and the Nickel Dumps – Reforming Working Women's Recreation.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; his4443; histoire; histoire des femmes*; histoire et politique; loisirs des femmes*; new york; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail; travail des femmes*